Dietary overlap in inshore notothenioid fish from the Danco Coast, western Antarctic Peninsula - Casaux, Ricardo Jorge; Barrera Oro, Esteban
We carried out a dietary overlap analysis between notothenioid species by examining the stomach contents of more than 900 specimens collected in a fish assemblage at the Danco Coast, western Antarctic Peninsula, in the summer of 2000. Prey reoccurrences among fish species were 32.2%, with krill Euphausia superba, salps and the gammaridean Prostebeingia longicornis the most reoccurring prey. The diet similarity between species pairs was lower than 55%, in accordance with similar fish assemblages in the South Orkney Islands, the South Shetland Islands and the Antarctic Peninsula. Whereas at those localities the higher prey overlap was between krill-feeding fish species, at the Danco Coast it was between Trematomus bernacchii and Lepidonotothen nudifrons, Notothenia coriiceps and Notothenia rossii, Notothenia coriiceps and Parachaenichthyis charcoti, and Trematomus newnesi and Notothenia rossii, which shared primarily gammaridean amphipods, algae, fish and krill, respectively. Krill is normally the main prey of fish in summer in inshore waters of the western Antarctic Peninsula, but its density in January/February 2000 was notably lower than in previous years. Therefore, at the Danco Coast, under conditions of krill shortage, most of the notothenioid species foraged more intensively on alternative prey, such as gammarideans, fish and algae. The difference between areas in the pattern of dietary overlap might be related to differences in prey availability between years and to the degree of competition for targeted prey. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Barrera Oro, Esteban. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina